Effect of Different Doses of Doxorubicin on Pituitary Gland and Some Testicular Function in Adult Male Rabbits: Baraa N. AL-Okaily@; Ammar A. Al-Haddad and Ahmed D. Salman - AL-Okaily, Baraa N. (The Iraqi Journal of Veterinary Medicine, 2013)
The present study was designed to search out the effect of different doses of doxorubicin some functions of pituitary gland and testes in adult male rabbits. Twenty adult male rabbits were randomly divided into four equal groups and treated for 28 days as follows: first group (control) were injected with normal saline; second group (GI) were injected with doxorubicin 3 mg/ kg B.W., while animals in the third group (GII) and fourth group (GIII) injected with 3.5 and 4 mg/ kg body weight of doxorubicin respectively, all animals were injected twice a week via ear vein. At the end of experiment fasting blood (8-10 hrs) samples were collected. Blood was drawn by cardiac puncture technique and serum was collected for measuring the hormones, Follicular Stimulating Hormone (FSH), Luteinizing Hormone (LH), and Testosterone (T). In addition, sections from pituitary gland and testes were taken for histopathological studies. The results showed significant increase (P<0.05) in serum FSH, LH and T levels in group (GIII) as compared to GI, GI and control groups. Beside significant increases in T levels was observed in GII as compared to control group. Sever histopathological changes was observed in testes including thickness of basement membrane, protienous material in lumen of somniferous tubules and pituitary gland showed fibrosis, faculation of epithelial cell in all treated groups. In conclusion different doses of doxorubicin have detrimental effect on pituitary gland and male reproductive system of rabbits